KETERAMPILAN KEPEMIMPINAN KEPALA SEKOLAH DAN BUDAYA SEKOLAH PADA SMA TERPILIH DI KOTA JAMBI - INDONESIA - Regidor G. Gaboy; Rizki, Reffy Ananda (SYAIKHONA: Jurnal Magister Pendidikan Agama Islam, 2023)
This quantitative study explored the leadership skills of the six principals in selected public senior high schools in Jambi City, Indonesia. Principals’ leadership skills in terms of setting instructional direction, teamwork, sensitivity, judgement, results orientation, organizational ability, oral communication, written communication, development of others, and understanding own strengths and weaknesses were assessed by the principals themselves and of the 159 public school teachers from their respective school. The difference as regards the leadership skills of the principals as perceived by themselves and of the teachers was also determined and the relationship between the principals’ self perceived leadership skills and of the teachers to school culture was also determined. Findings revealed that there was a positive correlation correlation between setting instructional direction skill and self- determination/efficacy (r=.864, p<.05), teamwork skill (r=.852, p<.05), and results orientation skill and affiliative collegiality (r=.956, p< .001).